Endophytic Bacillus Bacteria Living in Sugarcane Plant Tissues and Telchin licus licus Larvae (Drury) (Lepidoptera: Castniidae): The Symbiosis That May Open New Paths in the Biological Control - Rocha, Francine Yuriko Otsuka; Negrisoli Júnior, Aldomário Santo; de Matos, Gustavo Feitosa; Gitahy, Patrícia de Medeiros; Rossi, Carolina Nachi; Vidal, Marcia Soares; Baldani, José Ivo (Frontiers in Microbiology, 2021)
Bacteria of the genus Bacillus can colonize endophytically and benefit several crops including the control of some pest orders. In view of the benefits provided by these microorganisms and in order to find out an efficient biotechnological control for the giant borer, our interest in studying the microorganisms in symbiosis with sugarcane and the giant borer has arisen, since there is no efficient chemical or biological control method for this pest. Therefore, endophytic Bacillus strains were isolated from three sugarcane niches (apoplast fluid, central internode cylinder and roots) and also from the giant borer larvae living inside sugarcane varieties grown in the Northeast region of Brazil. The taxonomical characterization (16S rRNA) of 157 Gram-positive isolates showed that 138 strains belonged to the Bacillus genus. The most representative species were phylogenetically closely related to B. megaterium (11.5%) followed by B. safensis (10.8%), B. cereus (8.9%), B. oleronius (8.9%), B. amyloliquefaciens (7.0%) and B. pacificus (6.4%). BOX-PCR analyses showed very distinct band pattern profiles suggesting a great diversity of Bacillus species within the sugarcane niches and the digestive tract, while the B. cereus group remained very closely clustered in the dendrogram. According to XRE biomarker analysis, eleven strains (FORCN005, 007, 008, 011, 012, 014, 067, 076, 092, 093 and 135) correspond to B. thuringiensis species. Additional studies using conserved genes (glp, gmk, pta and tpi) indicated that most of these strains were phylogenetically closely related to B. thuringiensis and may be considered different subspecies. In conclusion, this study suggests that the culturable Bacillus species are greatly diversified within the plant niches and showed Bacillus species in the digestive tract of the giant borer for the first time. These results open new perspectives to understand the role and functions played by these microorganisms in symbiosis with this pest and also the possibility of developing an efficient biological control method for the giant borer using strains identified as the B. thuringiensis species.